Proceedings of the Second Workshop on Backgrounds at the Machine Detector Interface Honolulu, Hawaii, 21-22 March 1997 (World Scientific Publishing Co. Pte Ltd., 1998)
"At high luminosity, bottom, charm and ? factories, synchrotron radiation and lost particles due to beam-gas interaction cause huge backgrounds to detectors, posing problems in trigger rates, radiation damage and efficiency. Studies of such effects have been made and are reported in this book."--Publisher's website